ChemInform Abstract: Chemoselective Cross‐Coupling Reactions with Differentiation Between Two Nucleophilic Sites on a Single Aromatic Substrate. Issue 15 (25th March 2013) - Linshoeft, Julian; Heinrich, Annika C. J.; Segler, Stephan A. W.; Gates, Paul J.; Staubitz, Anne
Abstract Based on bis‐stannyl thiophene the thiophene derivative (I) is prepared through monolithiation and in situ Li‐B exchange.